2018
DOI: 10.1155/2018/8615435
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Suppresses Invasiveness of Endometrial Cells through Reduction of Fascin-1

Abstract: Objective Autophagy has been reported to be involved in the development of various disorders such as neurodegenerative and metabolic diseases and tumors. Autophagy activators and inhibitors are also potential therapeutics for these diseases. However, the mechanism of autophagic involvement in different diseases is not the same, and the role of autophagy in endometriosis (EM) has not yet been elucidated. This research investigated the mechanism by which autophagy acts in EM, with the aim of establishing a theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Increased autophagy and decreased invasiveness in pulmospheres obtained from WFA-treated bleomycin-exposed mice demonstrated that induction of autophagy inhibited invasiveness. These results and those of other studies demonstrated that autophagy indirectly regulates cellular invasiveness (63).…”
Section: Discussionsupporting
confidence: 86%
“…Increased autophagy and decreased invasiveness in pulmospheres obtained from WFA-treated bleomycin-exposed mice demonstrated that induction of autophagy inhibited invasiveness. These results and those of other studies demonstrated that autophagy indirectly regulates cellular invasiveness (63).…”
Section: Discussionsupporting
confidence: 86%
“…Actually, there exist contrary opinions on whether autophagy is stronger in normal tissue or endometriotic tissues. Some researchers proved that autophagy level were significantly reduced in eutopic ESCs, ectopic ESCs, serum and peritoneal fluid from women with endometriosis compared with normal women 12, 15, 17-20, while others held the opposite views, revealing that autophagy showed a significant up-regulation in ectopic endometrium compared with normal endometrium 21-24. Similarly, the comparison of autophagy in ectopic ESCs and eutopic ESCs was also not completely clear and consensus 11, 15, 21-24.…”
Section: The Level Of Autophagy In Endometriummentioning
confidence: 99%
“…By inhibiting the activity of autophagy in endometriotic stromal cells, MK2206 (an AKT inhibitor) and chloroquine markedly reduced cell growth and regrowth after discontinuation of treatment, and reduced the size of endometriotic implants, indicating that autophagy played a cytoprotective role in endometriosis 96. Autophagy was also reported to inhibit the proliferation and colony formation, and the growth of filopodia of the endometriotic cell line CRL-7566 through fascin-120. A newly identified tumor suppressor, PDCD4, can effectively inhibit the proliferation and colony-forming ability and suppress the migration and invasion ability of endometrial cells probably by inhibiting cell autophagy 68.…”
Section: Endometriosismentioning
confidence: 99%
“…More recently, other reports found that promotion of autophagy could impair the invasion of KRAS-transformed cells, while interrupting autophagy could counteract the inhibitory effect on the invasion of transformed cells, which was further demonstrated in mice bearing transformed cells-derived tumor xenograft by inducing autophagy 5,6. However, other reports demonstrated that cancer cells proliferation is related to autophagy elevation, possibly due to the increased metabolic and biosynthetic demands imposed by deregulated profiferation 2729…”
Section: Discussionmentioning
confidence: 99%
“…Iron oxide nanoparticles (IONs), a noncytotoxic reagent, could effectively induce a decrease of cell migration/invasion in K-ras transformed cells and endometrial cells, cytoskeleton and cell motility capacity were greatly affected after IONs incubation even at low iron concentration (0.1 mm) 5,6. In our previous study of PEGylated IONs (PION@E6), we demonstrated that IONs as nanocarriers to improve chlorin e6 (E6)-based sonosensitivity in impairment of cancer cells viability 7.…”
Section: Introductionmentioning
confidence: 99%